2013
DOI: 10.1186/1810-522x-52-56
|View full text |Cite
|
Sign up to set email alerts
|

Feeding spectra of bivalve mollusks Unio and Dreissena from Kanevskoe Reservoir, Ukraine: are they food competitors or not?

Abstract: Background: One of the most abundant freshwater invaders is Dreissena polymorpha which provide wide-ranging direct and indirect impacts on the invaded ecosystems. A particularly notable impact on benthic communities is the extinction of native mollusks of the order Unionida. However, the settlement of D. polymorpha on unionid's shells in Kanevskoe Reservoir did not increase native unionid mortality. Since the reason for the successful coexistence of native unionids and invading dreissenids in Kanevskoe Reservo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…In addition, it should be noted that some 20:1 acids are markers of mollusks [70]. However, the migratory species from the Keret River, C. lavaretus, did not have an explicitly higher level of Σ20:1, and lower level of 20:4n-6 than land-locked species.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, it should be noted that some 20:1 acids are markers of mollusks [70]. However, the migratory species from the Keret River, C. lavaretus, did not have an explicitly higher level of Σ20:1, and lower level of 20:4n-6 than land-locked species.…”
Section: Discussionmentioning
confidence: 89%
“…However, the migratory species from the Keret River, C. lavaretus, did not have an explicitly higher level of Σ20:1, and lower level of 20:4n-6 than land-locked species. In addition, it should be noted that some 20:1 acids are markers of mollusks [70]. Indeed, C. nasus from the Yenisei River, which consumed primarily mollusks, had a comparatively high level of Σ20:1.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other PUFAs, DHA is commonly absent or occurs only in trace levels in the majority of insect taxa (Stanley-Samuelson et al, 1988;Rumpold & Schluter, 2013;Sanchez-Muros et al, 2014; but see Lau et al, 2012), and in modest levels in terrestrial vertebrates (Hulbert, Rana & Couture, 2002;Valencak & Ruf, 2007), but occurs in high or moderate amounts in other noninsect aquatic invertebrates and fish Makhutova et al, 2013). We found that corixids, especially C. coleoptrata, had the highest mass-specific DHA content thus far reported for insects and, at 0.20-0.37 mg g À1 wet weight, were two to fourfold higher than other aquatic insects Kalacheva et al, 2013;Sushchik et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, utilisation of both suspended (i.e. water column) and benthic food resources could provide mussels with opportunistic dietary alternatives, depending on the relative availabilities of these resources over time (Nichols et al ., ; Makhutova et al ., ). Recent studies have demonstrated that consumers occupying lower trophic levels in freshwater ecosystems can rely to a significant extent on allochthonous OM originating in associated watersheds (Rounick, Winterbourn & Lyon, ; Caraco & Cole, ; Cole, ).…”
Section: Introductionmentioning
confidence: 99%